Alleviating Effects of AS1892802, a Rho Kinase Inhibitor, on Osteoarthritic Disorders in Rodents - Nobuaki Takeshita; Eiji Yoshimi; Chie Hatori; Fumiyo Kumakura; Nobuo Seki; Yasuaki Shimizu (Elsevier, 2011)
The effects of AS1892802, a selective Rho-associated coiled coil kinase (ROCK) inhibitor, on knee cartilage damage and pain behavior were examined in a rat model of osteoarthritis (OA). Monoiodoacetate (MIA) was intraarticularly injected into the right knee joints of rats. ROCK I and II mRNA levels increased in knee joints of MIA-injected rats. Our newly synthesized ROCK inhibitor, AS1892802, was injected into the ipsilateral knee or administered p.o. for 3 weeks. The compound dose-dependently and significantly inhibited of cartilage damage in the tibial plateau in a dose-dependent manner and decreased the weight distribution deficit associated with MIA injection. In addition, the compound also inhibited bradykinin induced pain responses in normal rats. In vitro, the compound could induce chondrocyte differentiation in a chondrogenic cell line and significantly inhibited IL-1β- or bradykinin-induced prostaglandin E2 production in a synovial cell line. AS1892802 prevents cartilage damage induced by MIA and has analgesic effects in rat pain models, suggesting that AS1892802 may be clinically useful for the treatment of OA.[Supplementary Figure: available only at http://dx.doi.org/10.1254/jphs.10319FP] Keywords:: osteoarthritis, Rho kinase inhibitor, cartilage, pain, inflammation